ChatGPT and English Language Pedagogy in Nigerian Universities: Sensemaking and Assessments - Tunde-Awe, Bolajoko Margaret (Universitas Kapuas, 2024)
Technology such as ChatGPT is central to effective instruction in English as a Second Language (ESL) pedagogy. However, language educators and students must have a shared understanding of its prospects to be used successfully in an academic setting. While extant studies have established its proliferation among students, this study investigated the sense-making of language educators as regards ChatGPT and its implications on assessment practices. A descriptive research design of the survey type was adopted for this study. The population of the study were forty-three university language educators and five hundred and five pre-service teachers who were purposively selected from two higher institutions in Ondo State, Nigeria. Self-structured questionnaire titled: Sense-making of ChatGPT among Language Educators Questionnaire (SCLEQ: r = 0.87) and Students’ Utilization of ChatGPT Questionnaire (SUCQ: r = 0.81). Three research questions were answered in this study. Findings revealed that students, to a very great extent, use ChatGPT to ace their essays (¯x=3.7) but then again, there is a gap-in-knowledge regarding its uses among university language educators (¯x=1.8). On the basis of these findings, the study recommended that language educators should get acquainted with AI tool and its applications in ESL pedagogy and also be creative on the best assessment mode given the reality on the ground.